Still life object photography - Zietsman, Petra (Bloemfontein: Central University of Technology, Free State, 1995)
Since 1839 photography has been a vital means of communication and expressiOn, being at once a science and an art, both aspects are inseparably linked. It can only be through the skilled hands of a photographer that photography can rise as an independent art form. "Conceptual photography is the photography of ideas - the representation of ideas through photography and the creation of new ideas about photography. It is the realm of the imagination, the territory of fantasy, the province of persuasion. it is images that intrigue the mind, as well as catch the eye. " (O'Connor 1989:87). The most important factor when producing a photograph of an object (studio still life, natural found) is to decide what you wish to say and to whom. The next great step is to decide what mood you wish to express. This is then accomplished by composition, lighting, choice of lens and camera, props and background. "Photographers in general, and still life photographers in particular, require a rudimentary working knowledge of chemistry, physics, mathematics, optics, art history, composition, colour and light, psychology, carpentry, plumbing, electronics and house painting. Additionally they should have strong backs. "
Thesis
Keywords: Still life photography; Photography Study and teaching - South Africa